Five problems for the moral consensus about sins - Ashfield, Mike (International journal for philosophy of religion, 2021)
A number of Christian theologians and philosophers have been critical of overly moralizing approaches to the doctrine of sin, but nearly all Christian thinkers maintain that moral fault is necessary or sufficient for sin to obtain. Call this the “Moral Consensus.” I begin by clarifying the relevance of impurities to the biblical cataloguing of sins. I then present four extensional problems for the Moral Consensus on sin, based on the biblical catalogue of sins: (1) moral over-demandingness, (2) agential unfairness, (3) moral repugnance, and (4) moral atrocity. Next, I survey several partial solutions to these problems, suggested by the recent philosophical literature. Then I evaluate two largely unexplored solutions: (a) genuine sin dilemmas and (b) defeasible sinfulness. I argue that (a) creates more problems than it solves and that, while (b) is well-motivated and solves or eases each of the above problems, (b) leaves many biblical ordinances about sin morally misleading, creating (5) a pedagogical problem of evil. I conclude by arguing that (5) places hefty explanatory burdens on those who would appeal to (b) to resolve the four extensional problems discussed in this paper. So Christian thinkers may need to consider a more radical separation of sin and moral fault.